A prospective study on vertical mattress suture and subcuticular suture skin closure techniques in inguinal hernia repair cases - R., Saranya; S., Padma; K., Manoj S. (International Surgery Journal, 2022)
Background: Sutures are used to keep tissues in place until enough healing has taken place to produce endogenous wound strength. The method of closure should be quick, simple, affordable, and successful while maximizing the cosmetic of the wound and patient outcomes. So, this study was an attempt to compare subcuticular and vertical mattress suture techniques in inguinal hernia repair. Methods: A prospective study was carried out among patients posted for inguinal hernia repair. The wound closure of the first 25 patients was done using a subcuticular suture and another by classical vertical mattress suture. Duration required for wound closure, complications, postoperative pain and cosmesis were assessed and analyzed using descriptive and inferential statistics. Results: The duration required for wound closure was higher in the subcuticular suture compared with the classical vertical mattress suture. There was no significant difference in post-operative pain, wound complications and wound cosmesis in both groups. Conclusions: Among cases with inguinal hernia repair there was no superiority in subcuticular and classical vertical mattress sutures from the patient side.